2019
DOI: 10.5582/bst.2019.01109
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown expression of <i>MECR</i>, a novel gene of mitochondrial FAS II inhibits growth and colony-formation, promotes apoptosis of hepatocelluar carcinoma cells

Abstract: Mitochondrial trans-2-enoyl-CoA reductase (MECR) is a protein-coding gene, and the protein encoded by this gene is an oxidoreductase that catalyzes the last step in mitochondrial fatty acid synthesis (mtFASII). Numerous studies have shown disorder of lipid metabolism is closely related with malignance, especially in liver cancer. Through pre-experiment, we found that the expression of MECR gene was highly expressed in hepatocelluar carcinoma (HCC) cell lines in vitro. This suggests that the MECR gene may play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Alteration in cell metabolism is an established hallmark of cancer 25 . Often cancer cells utilize multiple pathways and mechanisms involving different metabolites to support their survival, evade tissues and metastasis 25,26 . Lipid metabolism is altered by cancer cells transforming into malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alteration in cell metabolism is an established hallmark of cancer 25 . Often cancer cells utilize multiple pathways and mechanisms involving different metabolites to support their survival, evade tissues and metastasis 25,26 . Lipid metabolism is altered by cancer cells transforming into malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that Remodelin modulates MFAE and beta oxidation by decreasing levels MECR and ECHS1 . Both genes were shown to be overexpressed in cancer cells as numerous cancers utilize these genes to promote cell survival, cell proliferation, and metastasis through the accumulation of lipids 26,28‐30 . Although ECHS1 deficiency is shown to reduce lipid accumulation, and other studies in renal cancer reported that the presence of ECHS1 inactivates FAS, hence, increasing lipid accumulation 29‐31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockout of the mitochondrial 2-enoyl thioester reductase, Mecr , is lethal in mice due to a placental defect ( Nair et al, 2017 ), while the inducible knockout of Mecr specifically in Purkinje cells leads to loss of this cell population and recapitulates many phenotypes of MePaN syndrome, the human disease caused by Mecr mutation ( Gorukmez et al, 2019 ; Heimer et al, 2016 ; Nair et al, 2018 ). Similarly, Mecr knockdown has been shown to inhibit the growth of hepatocellular carcinoma cells ( Cai et al, 2019 ). While these detrimental phenotypes are clear, the molecular consequences of mtFAS loss remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the livers of mice with liver fibrosis, MECR as lipoic acid synthetic pathway enzymes were significantly reduced ( Luo & Shen, 2020 ). Moreover, MECR is reportedly crucial in many diseases, such as hepatocelluar carcinoma ( Cai et al, 2019 ), childhood-onset dystonia and optic atrophy ( Heimer et al, 2016 ). Meanwhile, a marked body of evidence from both cohort and case-control studies have indicated the significant relevance between the disorder of lipid levels and DR ( Das et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%